REPLACEMENT AND RETIREMENT ACCOUNTING AND RATE BASE VALUATIONS. - Krebs, Willlam S. (The Accounting Review, 1950)
Abstract In a previous article in the Accounting Review, attention was paid to the problem of what should be done when a utility shifts from retirement, or retirement reserve, accounting to depreciation accounting. Consideration was given to the formula for the rate base itself and, as well, to the procedure to follow when property was retired from service. Public service commissions are faced with still other problems. Some utilities have carried on, at least for some of their properties, a procedure which may well be referred to as replacement or betterment accounting, and which may have ramifications quite different from either retirement or depredation accounting. In following replacement accounting, assets are set up on the books at cost whenever they are acquired and are retained on the books at these figures indefinitely. Whenever replacements are made "in kind," the entire cost of the replacement, whether at higher or lower prices than at the outset, is charged to current operating expenses. Thus the investment account remains stationary unless the asset is retired and not replaced, in which case the investment account is written down. On the assumption that prices remain constant retirement accounting and replacement accounting give the same basic results. It is when prices change that the two part company. When replacements are not in kind, adjustment of the investment account is made.